2020
DOI: 10.3892/ijmm.2020.4701
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin‑β�4 induces angiogenesis in critical limb ischemia mice via regulating Notch/NF‑κB pathway

Abstract: Thymosin-β 4 (Tβ4) has been reported to exert a pro-angogenic effect on endothelial cells. However, little is known on the role and underlying mechanisms of Tβ4 on critical limb ischemia (cLI). The present study aimed therefore to investigate the mechanisms and pro-angiogenic effects of Tβ4 in cLI mice. Tβ4 overexpression lentiviral vector was first transfected into HUVEC and CLI mice model, and inhibitors of Notch pathway (dAPT) and NF-κB pathway (BMS) were also applied to HUVEC and CLI mice. Subsequently, MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Furthermore, irisin decreased the expression of NF-κB and pNF-κB, which are classical regulators in angiogenesis, inflammation, and neuron apoptosis. 16 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, irisin decreased the expression of NF-κB and pNF-κB, which are classical regulators in angiogenesis, inflammation, and neuron apoptosis. 16 , 49 …”
Section: Discussionmentioning
confidence: 99%
“…After cell infection with Tβ4 overexpression vectors for 6 h, the lentiviruses‐contained medium was displaced with complete medium, followed by 48‐h culture at 37°C for subsequent experimentation. [ 12 ]…”
Section: Methodsmentioning
confidence: 99%
“…After cell infection with Tβ4 overexpression vectors for 6 h, the lentiviruses-contained medium was displaced with complete medium, followed by 48-h culture at 37°C for subsequent experimentation. [12] LX-2 cells were allocated to the following 8 groups: blank group (normal LX-2 cells), TGF-β1 group (LX-2 cells stimulated with 5 ng/mL TGF-β1 for 24 h), TGF-β1 + oe-NC group (based on the TGF-β1 group, LX-2 cells treated with NC lentiviral infection for 6 h), TGF-β1 + oe-Tβ4 group (based on the TGF-β1 group, LX-2 cells treated with Tβ4 lentiviral infection for 6 h), TGF-β1 + MI group (treated with 10 μM MAPK inhibitor SB2035805 for 1 h, followed by stimulation with 5 ng/mL TGF-β1 for 24 h), TGF-β1 + dimethyl sulfoxide (DMSO) group (cultured with DMSO solvent for 1 h, followed by stimulation with 5 ng/mL TGF-β1 for 24 h), TGF-β1 + oe-Tβ4 + DMSO group (based on the TGF-β1 + oe-Tβ4 group, LX-2 cells supplemented with DMSO solvent for 1 h), TGF-β1 + oe-Tβ4 + MA group (based on the TGF-β1 + oe-Tβ4 group, LX-2 cells treated with 10 nmol/L MAPK activator U-46619 for 1 h). MAPK inhibitor SB203580 and MAPK activator U-46619 were provided by Calbiochem.…”
Section: Cell Treatment and Groupingmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Tb4 inhibited the proliferation and activation of hepatic stellate cells (HSCs), attenuated liver fibrosis by inhibiting Notch signaling, and markedly reduced expression levels of Notch2 and Notch3, which were increased in the liver cells (42). Furthermore, Tb4 enhanced HUVEC viability, angiogenesis, and migration, as well as promoted the expression of angiopoietin 2, VEGF A, Notch3, and other cytokines in HUVECs in a mouse model of critical limb ischemia (43). In addition, Takeshitak et al (44) reported that endothelial-specific Notch1 knockdown mice had impaired neovascularization after hindlimb ischemia, and Notch1 induced angiogenesis without VEGF involvement (45).…”
Section: Notch Pathwaymentioning
confidence: 99%